STUDI PENGARUH PEMASANGAN SPIKE UNTUK MELINDUNGI SALURAN DISTRIBUSI TEGANGAN MENENGAH PADA PENYULANG BUDUK - I Kadek Dodik Darma Putra; I Gede Dyana Arjana I Gede Dyana Arjana; I Wayan Rinas (Program Studi Teknik Elektro UNUD, 2021)
Buduk feeder is a 20 Kv medium voltage distribution system that gets power supplyfrom the ship's substation and crosses large coastal areas and rice fields and is prone to naturalphenomena such as lightning. During 2018 there were 3 lightning disturbances. Based on thesedata, it is necessary to analyze the distribution channel failure at Buduk feeders, so thecontinuity of the distribution channel can be better. The performance of the Spike System iswhen a lightning surge occurs on the distribution channel, the Spike System directly transmitsthe lightning strike to the ground. Based on the data analysis, it is necessary to add a Spikeprotection system to the Buduk Feeder to maintain the continuity of electric power.The methodused in this research is to collect data in the form of a single line diagram, disturbance data dueto lightning strikes at Buduk feeders. Next, compared the Buduk feed line before Spikeinstallation and after spike installation. First, analysis of technical data and the channelperformance before spike installation. Second, proceed with channel analysis after theinstallation of the Spike. Third, to analyze the causes of failure due to lightning strikes on thefeeders. The results obtained after the installation of the Spike system, the number ofdisturbances due to lightning surges, both induction and direct strikes, decreased in 2019 withthe number of interruptions one time.